2017
DOI: 10.15850/amj.v4n2.1086
|View full text |Cite
|
Sign up to set email alerts
|

Five Years Study of Recurrent Febrile Seizure Risk Factors

Abstract: Background: Nearly one-third of febrile seizure patients suffered recurrent febrile seizures. Several risk factors contribute to this recurrence, namely young age, family history of febrile seizures, low body temperature and rapid duration of fever before onset of seizures. Recently, the types of seizure and gender have been stated increasing risk of this recurrence. The objectives of this study was to identify the risk factors of recurrent febrile seizures. Methods: A descriptive study was carried out by retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
(19 reference statements)
3
1
1
1
Order By: Relevance
“…This study found that recurrence of febrile seizures was more common in male patients, gender ratio of male to female was 1.5:1. These result is in line with previous studies that found out the gender of patients who experienced recurrence of febrile seizures were mostly male 5,7,8,9,14 . Different results were found in other studies which showed the gender of recurrence of febrile seizures were mostly female 4,10 .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This study found that recurrence of febrile seizures was more common in male patients, gender ratio of male to female was 1.5:1. These result is in line with previous studies that found out the gender of patients who experienced recurrence of febrile seizures were mostly male 5,7,8,9,14 . Different results were found in other studies which showed the gender of recurrence of febrile seizures were mostly female 4,10 .…”
Section: Resultssupporting
confidence: 93%
“…The difference in the fever interval for each child was due to the seizure threshold for each child was different 20 . This result is in line with previous studies which found that fever intervals of patients who experienced recurrence of febrile seizures were mostly 24 hours 10,14 . Other studies have found febrile seizures recurrence on patients who experienced fever similar intervals between 24 hours or > 24 hours 10 .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Research results in several journals have different results. In a study conducted in Indonesia, precisely at RSHS Bandung, out of 58 children with recurrent febrile seizure, 38 (65%) of those suffer complicated febrile seizure, and 16 children (28%) sufer simple febrile seizure, while in 4 children (7%) the type of febrile seizure cannot be identified (8) . This is in similar to the results of this study.…”
Section: Discussionmentioning
confidence: 99%